Transverse and longitudinal fluid flow modelling in fractured porous media with non-matching meshes - Damirchi, Behnam V.; Carvalho, Marcelo R.; Bitencourt, Luís A. G.; Manzoli, Osvaldo L. [UNESP]; Dias-da-Costa, Daniel (Wiley, 2021)
A new discrete fracture model is introduced to simulate the steady-state fluid flow in discontinuous porous media. The formulation uses a multi-layered approach to capture the effect of both longitudinal and transverse permeability of the discontinuities in the pressure distribution. The formulation allows the independent discretisation of mesh and discontinuities, which do not need to conform. Given that the formulation is developed at the element level, no additional degrees of freedom or special integration procedures are required for coupling the non-conforming meshes. The proposed model is shown to be reliable regardless of the permeability of the discontinuity being higher or lower than the surrounding domain. Four numerical examples of increasing complexity are solved to demonstrate the efficiency and accuracy of the new technique when compared with results available in the literature. Results show that the proposed method can simulate the fluid pressure distribution in fractured porous media. Furthermore, a sensitivity analysis demonstrated the stability regarding the condition number for wide range values of the coupling parameter.
Keywords: coupling finite elements; embedded discontinuity approach; fluid flow; fractured porous media; transverse fluid flow